Strategy for constructing highly stable supercapacitors: Channeling of thin-layer polyaniline to enhance pseudo-capacitance of the CuS/polyaniline@MoS2 composites. (1st March 2022) - Dai, Juguo; Luo, Lili; Tang, Zhenbin; Lv, Yan; Xie, Hongmei; Zuo, Haiyan; Yang, Chunying; Wang, Xiaohong; Fan, Mizi; Xu, Yiting; Dai, Lizong
Abstract: How to achieve an effective coupling of inorganic materials and highly efficient electron transfer inside a composite material is a crucial issue in the application of multiple-inorganic composite materials for supercapacitors. Herein, a facile strategy of using a thin-layer polyaniline for the construction of electron transfer channels within the multiple-inorganic composites is proposed. Benefiting from the polyaniline acting as a "bridge" for electron transfer and proper interaction between components of composites, CuS/PANI@MoS2 (CSPM) composites electrode is equipped with excellent specific capacitance (759.2 F g −1 at 1 A g −1 ) and cycle stability (92.1% capacitance retention after 6000 cycles) in the three-electrode systems. Asymmetric supercapacitor (ASC) devices assembled by the CSPM composites achieve a specific capacitance of 166.7 F g −1 at 1 A g −1, and the capacitance and coulombic efficiency drop by 14.5% and 4.0% after 5000 cycles, respectively. Impressively, the ASC devices achieve an energy density of 39.1 Wh kg −1 at a power density of 659.9 W kg −1 . Furthermore, the theoretical calculations verify that the surface-capacitive contribution of CSPM composites is improved with thin-layer polyaniline channeling (24% higher than CuS@MoS2 (CSM) composites at 100 mV s-1). This strategy will provide a new potential way towards the effective coupling of inorganic materials. Graphical abstract: Image 1